Dielectric properties of Ba₆₋₃ₓNd₈₊₂ₓTi₁₈0₅₄ ceramics - Lee, Chian Heng (2014)
In this research, high dielectric constant material especially in microwave frequency region was investigated. Pure barium titanate showed low dielectric constant value at high frequency region. In order to improve the properties, rare earth dopant was introduced to this material. The doping mechanism of neodymium ion on barium titanate could be promising a new material for applications in miniature microwave technology and mobile communication systems. The processing of the material always influences materials properties. Therefore, microstructural and complex permittivity of Ba6-3xNd8+2xTi18O54, with x=0.15 ceramics at different sintering temperatures were investigated. The phenomenon of polarization produced by the applied electric field was studied. The samples were prepared by the wet solid state method and sintered at a temperature range from 600°C to 1300°C. Sintering effects on the crystallite structure and surface morphology were studied and characterized by XRD and FESEM. The transformation of majority of the phases in the system from barium titanate to barium neodymium titanate was confirmed by XRD pattern due to change in sintering temperature. The shrinkage of each sintered ceramic was determined compared with the original dimension. The change in sample densities was determined using Archimedes’ method. BNT ceramic with highest sintering temperature obtained full densification. This is confirmed by the micrograph from FESEM, which showed grains are in rectangular shape. Two activation energies of 0.0698 eV for low sintered ceramics and 0.3348 eV for high sintered ceramics were observed by using estimated diffusion process.The dielectric properties with respect to the frequency from 1 MHz to 1.5 GHz were measured using the Impedance Analyzer, and the results were compared and analyzed. The highest dielectric constant and lowest loss tangent were defined among the samples.The BNT ceramic sintered at 1300°C obtained the highest dielectric constant of 30 at 1 GHz and 0.09 for loss tangent. The dielectric constant of this ceramic also showed almost independent of frequency. The complex dielectric modulus was used to differentiate the contribution of the grain and grain boundary. The results showed the semicircular arc changing when sintering temperature increased due to the influence of the secondary phases. For further investigation, BNT ceramic with x=0.25 was fabricated in order to compare with BNT x=0.15 at low frequency region and temperature effect. Higher Nd dopant definitely decreased the dielectric valuefrom 26.5 for BNT x=0.15 to 25.9 for BNT x=0.25 at 1 MHz at room temperature, but both ceramics showed independence of temperature and frequency. The desirable characteristics of Ba6-3xNd8+2xTi18O54for x=0.15 sintered at 1300°C Cinclude high dielectric constant of 30, low loss tangent of 0.09, and high quality factor developed a new field for electronic applications.